2019
DOI: 10.1101/2019.12.22.886556
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aerobic heterotrophy and RuBisCO-mediated CO2metabolism in marineThaumarchaeota

Abstract: 1Thaumarchaeota constitute an abundant and ubiquitous phylum of Archaea that play critical 2 roles in the global nitrogen and carbon cycles. Most well-characterized members of the phylum 3 are chemolithoautotrophic ammonia-oxidizing archaea (AOA), which comprise up to 5 and 20 % 4 of the total single-celled life in soil and marine systems, respectively. Using two high-quality 5 metagenome-assembled genomes (MAGs), here we describe a divergent marine thaumarchaeal 6 clade that is devoid of the ammonia-oxidation… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
2
2
0
Order By: Relevance
“…The presence of a large-subunit RuBisCO homolog (rbcL) in the HMT genomes is a notable feature of this group. We identified this gene in 4 of 5 HMT MAGs (missing only in HMT_AABW); it is also present in the ASW8 MAG, as previously reported (24). A phylogenetic analysis of the HMT RuBisCO homologs placed it with other form III-a members of this protein family, albeit with long branches that demonstrate it is divergent from any previously identified homolog (Fig.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…The presence of a large-subunit RuBisCO homolog (rbcL) in the HMT genomes is a notable feature of this group. We identified this gene in 4 of 5 HMT MAGs (missing only in HMT_AABW); it is also present in the ASW8 MAG, as previously reported (24). A phylogenetic analysis of the HMT RuBisCO homologs placed it with other form III-a members of this protein family, albeit with long branches that demonstrate it is divergent from any previously identified homolog (Fig.…”
Section: Resultssupporting
confidence: 76%
“…However, AMPase, a key enzyme of the AMP salvage pathway responsible for generating R15P, could not be identified in the HMT genomes. This was also reported for the ASW8 MAG (24), where those authors suggested that R15P is generated from phosphoribosyl pyrophosphate by a Nudix hydrolase. Homologs for all genes in this proposed pathway cyclization are present in the HMT genomes (Fig.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations